Anti-HTLV-1/2 IgG antibodies in the breastmilk of seropositive mothers - Rosadas,de Oliveira C; Woo,T; Haddow,J; Rowan,A; Taylor,G (Microorganisms, 2021)
Background: HTLV-1/2 mother-to-child transmission (MTCT) is an important route for the maintenance of HTLV-1/2 within populations and disproportionally contributes to the burden of HTLV-1-associated diseases. Avoidance of breastfeeding is the safest recommendation to prevent MTCT. Due to the benefits of breastfeeding, alternative methods that would allow seropositive mothers to breastfeed their babies are needed. There is limited knowledge about HTLV-1/2 infection and breastmilk. Methods: Paired blood and milk samples collected from HTLV-1/2 seropositive mothers were tested for HTLV-1 proviral load (PVL) quantification and for the detection of anti-HTLV-1/2 IgG. Results: All breastmilk samples had detectable anti-HTLV-1/2 IgG. HTLV-1/2 proviral DNA was detected in all samples except for one. HTLV-1 PVL and IgG binding ratio (BR) was similar in milk and plasma. However, antibody titer was significantly higher in blood (Median (95%CI): Milk:128 (32–512); Plasma:131,584 (16,000–131,584), p < 0.05). There was a strong correlation between HTLV-1 PVL, anti-HTLV-1/2 IgG BR, and titer when comparing milk and blood. PVL did not correlate with antibody BR nor titer in blood or milk. Conclusions: Anti-HTLV-1/2 IgG are present in milk in the same proportion as blood but in lower quantity. PVL in milk correlates with blood.